2022
DOI: 10.1111/cpr.13221
|View full text |Cite
|
Sign up to set email alerts
|

FGF6 promotes cardiac repair after myocardial infarction by inhibiting the Hippo pathway

Abstract: Objectives: Myocardial infarction (MI) commonly occurs in patients with coronary artery disease and have high mortality. Current clinical strategies for MI still limited to reducing the death of myocardial cells but failed to replace these cells. This study aimed to investigate the role of fibroblast growth factor 6 (FGF6) in enhancing the proliferative potential of cardiomyocytes (CMs) after ischemic injury via the Hippo pathway.Materials and Methods: Expression of FGF6 protein was analysed in mice with MI in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…As an important member of the FGF family, FGF6 plays an important role in regulating cell proliferation, cell differentiation, angiogenesis and muscle production [ 30 , 31 ], but overexpressed FGF6 also promotes tumor progression. One study found that the interaction between LINC00265 and miR-4677–3p upregulated the expression of FGF6 to promote the proliferation, invasion and migration of bladder cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an important member of the FGF family, FGF6 plays an important role in regulating cell proliferation, cell differentiation, angiogenesis and muscle production [ 30 , 31 ], but overexpressed FGF6 also promotes tumor progression. One study found that the interaction between LINC00265 and miR-4677–3p upregulated the expression of FGF6 to promote the proliferation, invasion and migration of bladder cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cellular apoptosis directly contributed to cardiac dysfunction during MIRI. [21,22] Recent studies demonstrated that FGF10 may protect hepatocytes and renal tubular cells against apoptosis after I/R injury, [8,9] suggesting a possible role for FGF10 in the regulation of apoptosis after MIRI. To investigate this, mice were intraperitoneally injected with recombinant human FGF10 (rFGF10) protein (2mg/kg) daily for 2 weeks.…”
Section: Fgf10 Ameliorates Apoptosis Of Cardiomyocytes and Autophagos...mentioning
confidence: 99%
“…Cellular apoptosis directly contributes to cardiac dysfunction upon MIRI [21,22]. Recent studies demonstrated that FGF10 may protect hepatocytes and renal tubular cells against apoptosis after I/R injury [8,9], suggesting it may play a role in the regulation of apoptosis after MIRI.…”
Section: Fgf10 Ameliorates Apoptosis Of Cms and Accumulation Of Autop...mentioning
confidence: 99%